MULTISENSORS FOR WHOLE-CELL ANALYTICS - Tobehn-Steinhäuser, Ingo; Günther, Margarita; Görlandt, Stefan; Herbst, Steffen; Wünscher, Heike; Ortlepp, Thomas; Gerlach, Gerald (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2018)
Whole-cell biosensors, which can be used in the environmental protection and process measuring technology, in the biotechnology, food and pharmaceutical industry for the on-line control and monitoring of chemical and biochemical processes and for the fast detection of small amounts of solutes, are of great interest. These kind of biosensors comprise microorganisms like genetically modified yeast cells, which react on a specific stimulus, e.g. a residual amount of drugs in the measurement medium with a dependent fluorescence. The receptors of the cells detect specific signal molecules and stimulate the organism to produce a fluorescent protein. In this work, a combined impedimetric-optical read out was used, which can provide the reliable and long-term stable detection of a fluorescence signal accompanied by impedance measurements monitoring cell vitality and activity. A new challenge thereby is a special sensor design which enables the integration of excitation source, photodetector, interdigitated electrodes, and the fluidic system with an effective and long-term-stable packaging.